Inspecting the relation of search cost and search duration for new hires - Francesco Carbonero; Hermann Gartner (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institute for Economics, 2017)
Fixed search costs, i.e. costs that don't vary with search duration, can amplify the cyclical volatility of the labor market. To assess the size of fixed costs, we analyse the relation of search costs and search duration with data from Germany. Using an OLS regression we find that fixed search costs are nearly half of total search costs. If we use an instrumental variable estimation, it turns out that search costs are mainly fixed costs. Furthermore, we show that a search and matching model calibrated for Germany with fixed costs close to 100 percent can generate a labor market volatility that is consistent with the data.
Keywords: E32; J32; J63; J64; 330; search costs; search duration; unemployment volatility puzzle